2013
DOI: 10.3109/10826084.2013.782045
|View full text |Cite
|
Sign up to set email alerts
|

Relative Importance of Abstinence in Clients’ and Clinicians’ Perspectives of Recovery from Drug and Alcohol Abuse

Abstract: . (2013). Relative importance of abstinence in clients' and clinicians' perspectives of recovery from drug and alcohol abuse. Substance Use and Misuse, 48 (9), 683-690.Relative importance of abstinence in clients' and clinicians' perspectives of recovery from drug and alcohol abuse AbstractThis study collected data on drug and alcohol workers' (n = 55) and clients' (n = 139) perspectives on what constitutes a "recovery" from substance use disorder. Data were collected during 2010 from four residential faith-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…This programme involves skills training, psycho-education, 12-step based interventions and individual case management and counselling. Further information regarding the programme can be found in other studies (Deane et al, 2014;Maffina et al, 2013). Funding for the programme consists of on 30 per cent government funding, 30 per cent Salvation Army funding, 30 per cent client contribution (often welfare benefits) and 10 per cent other donations made to The Salvation Army.…”
Section: Participantsmentioning
confidence: 99%
“…This programme involves skills training, psycho-education, 12-step based interventions and individual case management and counselling. Further information regarding the programme can be found in other studies (Deane et al, 2014;Maffina et al, 2013). Funding for the programme consists of on 30 per cent government funding, 30 per cent Salvation Army funding, 30 per cent client contribution (often welfare benefits) and 10 per cent other donations made to The Salvation Army.…”
Section: Participantsmentioning
confidence: 99%
“…In the UK, individuals seeking treatment also often identify abstinence as their primary goal [7], and even the only change they hope to achieve [8]. In a recent survey, the majority of staff and clients in a treatment programmed in Australia were of the opinion that to remain in recovery means to remain abstinent from all drugs and alcohol [9]. In a multiple-choice survey, more than three quarters of individuals in America and Australia who self-identified as in recovery endorsed 'total abstinence' as their personal goal and definition of recovery [5,10].…”
Section: Different Meanings Of "Recovery"mentioning
confidence: 99%
“…Involvement in religious and self-help groups in the community consistently shows a modest positive relationship with abstinence [38][39][40]. Religious and spiritual factors have been said to be amongst the three most important factors in recovering from heroin use in Glasgow [21,41] and are rated more important as time in recovery increases [9]. However, many individuals entering addiction treatment show lower levels of spiritual or religious involvement relative to the general population.…”
Section: Recovery As Affiliation With Self-help Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional definitions of addiction recovery often focus on individuals abstaining from substances . However, research has shown that service users perceive recovery as involving more than just abstinence , and it is recognised that many other internal and external factors have a significant impact on an individual's recovery journey . These additional factors are captured by the term ‘recovery capital’, which is an overarching concept used to describe the multiple resources people use to aid their recovery from substance addiction .…”
Section: Introductionmentioning
confidence: 99%